Secularism and Its Challenges to Islamic Education: A Historical and Philosophical Analysis of Islamic Education - Lilik Qonitah; M. Sugeng Solehuddin (Social Journal of Studies in Education, 2026)
Secularism is often discussed in Islamic education studies in a normative manner, primarily as an ideology perceived to be incompatible with religious teachings. Previous studies tend to examine secularism either from the perspective of Western historical development or from Islamic normative critiques, without sufficiently integrating historical analysis with the philosophical framework of Islamic education. This article aims to analyze the historical development of secularism and its influence on the Muslim world, to examine how Islamic educational philosophy conceptualizes secularism, and to explore the implications of secularism for contemporary Islamic education. This study employs a qualitative approach through critical library research, drawing on classical and contemporary literature, with particular emphasis on peer-reviewed journal articles and works of modern Muslim thinkers. The conceptual framework is grounded in an integrative Islamic epistemology that views knowledge, moral values, and spirituality as inseparable. The findings indicate that secularism emerged from specific Western historical contexts and entered the Muslim world through colonialism and modernization, resulting in epistemological tensions within Islamic educational systems. Islamic educational philosophy views secularism as problematic due to its separation of knowledge from transcendent values, which has contributed to educational dualism and identity crises. This article contributes to Islamic education scholarship by emphasizing the need for a reconstructive and integrative educational paradigm that engages modernity critically while preserving its spiritual foundations.